Cortactin expression: Association with disease progression and survival in oral squamous cell carcinoma. Issue 12 (20th November 2018) - Horn, Dominik; Gross, Madeleine; Dyckhoff, Gerhard; Fuchs, Jennifer; Grabe, Niels; Weichert, Wilko; Herpel, Esther; Herold‐Mende, Christel; Lichter, Peter; Hoffmann, Jürgen; Hess, Jochen; Freier, Kolja
Abstract: Background: Cortactin (CTTN) is located on chromosome 11q13 and is associated with invasiveness in various cancer entities. CTTN protein expression could be a prognosticator of oral squamous cell carcinoma (OSCC) in terms of recurrence and survival. Methods: CTTN‐dependent invasion was performed using migration assay in human papillomavirus‐negative head and neck squamous cell carcinoma (HNSCC) cells. Cortactin protein analysis in tissue microarrays was used for correlation with clinical parameters, as well as for survival analysis. Gene expression profiling in HNSCC cells was performed to unreveal CTTN signaling. Results: Knockdown of CTTN in HNSCC cells showed less invasion in vitro. Gene expression profiling showed various deregulated genes known to be involved in progression. We confirmed the link between CTTN overexpression and progression in a large clinical cohort. High expression was associated with worse overall and progression‐free survival. Conclusions: We propose CTTN for managing OSCC in terms of adjuvant therapy and aftercare. Furthermore, our study reveals new potential targets in CTTN signaling for individualized OSCC therapy.